The Traditional Anecdote: What Did Lithuanians Find Funny in the End of the 19th–the Middle of the 20th Century? - Bandoriūtė, Salomėja (Tautosakos darbai, 2015)
The author of the article discusses the main themes of humor prevailing in the end of the 19th – beginning of the 20th century, and targets of mockery in the anecdotes. Seeking to answer the question, what Lithuanians during this period found funny, it was noted that humor reflects the relevant social issues and is usually based on certain stereotypic assumptions directed at some social groups. In the anecdotes, mockery is most frequently directed at three social groups: women, foreigners, and persons of higher social rank. So it can be assumed that humor is born whenever the opposition between us and them can be discerned. The analysis also proves that joking on obscene topics is rather common; this is based on the possibility provided by the occasion of the humor-making to express one’s inappropriate opinions on the tabooed topics, thus in a way breaking free from the socially established norms. The article yields rather ambivalent conclusions: it would hardly be right to assume that Lithuanians in the end of the 19th – beginning of the 20th century were all thinking stereotypically, and were foul-mouthed nationalists, atheists, and antifeminists; yet one can rightfully maintain that humor was, is and will always be a form of mockery directed at certain people and social groups.
Keywords: -